The Main Framework of Ancient Chinese Management Thought from the Perspective of Traditional Culture - Ani, Dou (Transactions on Social Science, Education and Humanities Research, 2024)
Ancient Chinese management philosophy is an important component of traditional Chinese culture, reflecting the thinking and summary of management practices by ancient Chinese people. This article summarizes the core viewpoints of major schools of thought such as Confucianism, Taoism, and Legalism from the perspective of traditional culture, as well as their implications for modern management. Through in-depth exploration of ancient management ideas, we can better understand the values and management concepts of traditional Chinese culture, and provide inspiration and reference for contemporary management practices.